DEVELOPMENT OF LEARNING DEVICE BASED ON PROBLEM BASED LEARNING TO FACILITATE THE MATHEMATICAL PROBLEM SOLVING STUDENT ABILITY ON ALGEBRA FORM OPERATIONS MATERIAL - Chindi Anggraini; Susda Heleni; Sakur (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2021)
This research is motivated by the teacher existence for the availability of mathematics learning instruments to support the learning process in the classroom according to the 2013 Curriculum. This research aims to produce a mathematical learning instruments based on Problem Based Learning (PBL) to facilitate the mathematical problem solving ability of seventh grade students of junior high school valid and practical on counting operation of algebra form topic. The development model used in this study is the 4-D model which consists of four stages of development, namely define, design, develop, and disseminate. Learning tools that have been developed are validated by three validators and revised according to the suggestions of the validator. The average result of syllabus validation analysis is 3,89 by category very valid, RPP 3,83 by category very valid, and LAS 3,79 by category very valid. The results of this validation analysis indicate that the syllabus and RPP is worth to using. LAS that has been valid then tested in small groups with test subjects of 6 grade VII students of SMP Negeri 25 Pekanbaru. The average result of the small group trial data analysis was 3,30 and categorized as very practical. Based on the results of data analysis and discussion, it can be concluded that the learning instruments developed can facilitate students to develop their mathematical problem solving skills and are suitable for use as a learning resource for students in learning. Keywords : Mathematics Learning instruments, Problem Based Learning (PBL), Mathematical Problem Solving Ability, counting operation of algebra.